2019
DOI: 10.1155/2019/6240505
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrointestinal Tumor Microenvironment: An Updated Biological and Clinical Perspective

Abstract: Gastrointestinal cancers are still responsible for high numbers of cancer-related deaths despite advances in therapy. Tumor-associated cells play a key role in tumor biology, by supporting or halting tumor development through the production of extracellular matrix, growth factors, cytokines, and extracellular vesicles. Here, we review the roles of these tumor-associated cells in the initiation, angiogenesis, immune modulation, and resistance to therapy of gastrointestinal cancers. We also discuss novel diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 268 publications
(261 reference statements)
0
6
0
1
Order By: Relevance
“…The tumor microenvironment remains to be the main battlefield between the tumor and host immunity, whereas the cross-talk between them seems to be important [ [34] , [35] , [36] , [37] ]. Immune cells infiltrated in tumor microenvironment not only receives the signals from tumor cells but also influence the malignant biological behavior of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor microenvironment remains to be the main battlefield between the tumor and host immunity, whereas the cross-talk between them seems to be important [ [34] , [35] , [36] , [37] ]. Immune cells infiltrated in tumor microenvironment not only receives the signals from tumor cells but also influence the malignant biological behavior of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…By secreting IL11, CAFs support distant metastasis through activating Glycoprotein 130 (GP130)/STAT3 signaling in PDAC cells ( 106 ). Also, increased STAT3 activity in CD11b+myeloid cells, motivates the local invasion of primary tumor cells into the blood or lymphatic vessels to move towards the metastatic sites and create pre-metastatic niche ( 107 ). Studies have shown that exosomes derived from PDAC can induce the formation of pre-metastatic niche in liver.…”
Section: Immune-related Cellular Biology In the Progression Of Pdacmentioning
confidence: 99%
“…Detailed insight into TME components and their role in de novo resistance to checkpoint blockade in GI cancers has recently been reviewed by Batista et al [19], and broadly outlined in Fig. 1.…”
Section: Pre-requisites For Anti-cancer Immunity and The Immune Landsmentioning
confidence: 99%